Perancangan dan Implementasi Alat Deteksi Kebocoran Gas LPJ Menggunakan Sensor MQ-2 Berbasis IOT: Penelitian - Siti Ramadani; Ridho Agusman; Utami Wardah Hafiz; Dicky Apdillah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
LPG gas is a widely used fuel in everyday life, but it carries a high risk of leaks, as it can cause fires or explosions. To mitigate this risk, this research aims to design and implement an LPG gas leak detection device using an IoT-based MQ-2 sensor. The MQ-2 sensor is used to detect LPG gas levels in the air. The data is then processed by a microcontroller and sent via the internet to an Android application. If the gas levels exceed safe limits, the system will issue an alarm and notification via the application. The research methods used included interviews, observations, literature review, and experiments. Test results indicate that the device is capable of effectively detecting LPG gas leaks and sending real-time notifications. This device is expected to help improve safety and prevent accidents caused by LPG gas leaks.